Mechanistic understanding of tungsten oxide in-plane nanostructure growth via sequential infiltration synthesis. Issue 7 (6th February 2018) - Kim, Jae Jin; Suh, Hyo Seon; Zhou, Chun; Mane, Anil U.; Lee, Byeongdu; Kim, Soojeong; Emery, Jonathan D.; Elam, Jeffrey W.; Nealey, Paul F.; Fenter, Paul; Fister, Timothy T.
Abstract : Tungsten oxide in-plane nanostructures have been fabricated by sequential infiltration synthesis, providing valuable insights into the growth process. Abstract : Tungsten oxide (WO3− x ) nanostructures with hexagonal in-plane arrangements were fabricated by sequential infiltration synthesis (SIS), using the selective interaction of gas phase precursors with functional groups in one domain of a block copolymer (BCP) self-assembled template. Such structures are highly desirable for various practical applications and as model systems for fundamental studies. The nanostructures were characterized by cross-sectional scanning electron microscopy, grazing-incidence small/wide-angle X-ray scattering (GISAXS/GIWAXS), and X-ray absorption near edge structure (XANES) measurements at each stage during the SIS process and subsequent thermal treatments, to provide a comprehensive picture of their evolution in morphology, crystallography and electronic structure. In particular, we discuss the critical role of SIS Al2 O3 seeds toward modifying the chemical affinity and free volume in a polymer for subsequent infiltration of gas phase precursors. The insights into SIS growth obtained from this study are valuable to the design and fabrication of a wide range of targeted nanostructures.